Sensitive whole mount in situ localization of small RNAs in plants - Ghosh Dastidar, Mouli; Maizel, Alexis (The plant journal, 2016)
Small RNAs, such as microRNAs (miRNAs), regulate gene expression and play important roles in many plant processes. Although our knowledge of their biogenesis and mode of action has significantly progressed, we still have comparatively little information about their biological functions. In particular, knowledge about their spatio-temporal expression patterns rely on either indirect detection by use of reporter constructs or labor-intensive direct detection by in situ hybridization on sectioned material. None of the current approaches allows a systematic investigation of small RNA expression patterns. Here, we present a sensitive method for in situ detection of miRNAs and siRNAs in intact plant tissues that utilizes both double-labeled probes and a specific cross-linker. We determined the expression patterns of several small RNAs in diverse plant tissues.